¿Hacia dónde va la ortopedia y traumatología cubana? - Machado Cano, María Julia (Mediciego, 2020)
We are pleased to recommend in this issue of MediCiego, the intervention: "Quo Vadis: Orthopedics and Traumatology" performed by Dr. Cs. Alfredo Braulio Ceballos Mesa, outstanding personality of Cuban medicine, education and research, at the XXVIII National Congress of Orthopedics and Traumatology,(1) sponsored by the Cuban Society of this specialty in 2019 and also disclosed at the XIX Provincial Conference of the Avileño Chapter on February 27 of this year